Feminist art and the maternal - Liss, Andrea (University of Minnesota Press, 2009)
Feminist motherhood is a surprisingly unexplored subject. In fact, feminism and motherhood have been often thought of as incompatible. Profound, provocative, and innovative, Feminist Art and the Maternal is the first work to critically examine the dilemmas and promises of representing feminist motherhood in contemporary art and visual culture. Andrea Liss skillfully incorporates theory with passionate personal reflections on the maternal, and in doing so she advances a fresh and necessary perspective on both feminism and art. Offering new research on works by well-known and emerging artists wh.